(untitled) (Polis (Santiago), 2018)
Acts of civil disobedience are part of a democratic rule of law and develop into mature societies that manage to process their conflicts by accepting that legally established laws and institutions can «fail», admitting a space for the construction of interpretations that differ from the prevailing whixh, nevertheless, claim to be fair. The widely held view that any act contrary to the law is always an illegal act that deserves punishment, both positively defined as well as social condemnation, admits another analysis from the perspective of civil disobedience. First, we present an analysis of the debate on the foundations of legitimate power. Second, an analysis of the limitations that from social sciences and law arise, in order to provide a different understanding of civil disobedience. Finally, a conceptual revision of different authors that examine the concept of civil disobedience.